HUBUNGAN EMPATI DENGAN PERILAKU PROSOSIAL PADA RELAWAN KSR PMI KOTA MEDAN - Istiana Istiana (Jurnal Diversita, 2016)
This study aims to determine the relationship of empathy and prosocial behavior in KSR PMI volunteers Medan. Subjects in this study were volunteers KSR PMI Medan which numbered 60 people. Aspects that are used as a measuring tool prosocial behavior, use the opinion of Baron and Bryne, namely Helping a Stanger Distress, deterring a wrongdoer and Resist. Aspects that are used as a measure of empathy, using the Davis opinion, namely Perspective taking, Emphatic Concern, Personal Distress, and Fantasy. Measuring instrument used is a Guttman scale consists of 36 items prosocial behavior (α = 0.936) and a Likert scale consists of 42 items empathy (α = 0.932). Data analysis using techniques r Product Moment. Based on data analysis, found that the hypothesis proposed in this study received, that there is a relationship between empathy and prosocial behavior in KSR PMI volunteers Medan. This is evidenced by the value or coefficient of correlation (???????????? = 0.328, p> 0.05), as well as empathy influence prosocial behavior in KSR PMI volunteers in Medan by 10.8%, further views from the calculation of hypothetical mean and the empirical mean and standard deviation is known that the level of prosocial behavior and empathy in KSR PMI volunteers Medan is high seen by the average empirical value is higher than the average value of the hypothetical empathy and prosocial behavior.